Morphology and multigene phylogeny revealed four new species of Geastrum (Geastrales, Basidiomycota) from China - Xin Yang; Yonggao Zhu; Songjing Duan; Xingxing Wu; Changlin Zhao (MycoKeys)
In the present study, four new species, Geastrum artocarpicola, G. fibulatum, G. sinense and G. trachelium collected from China, are proposed based on a combination of morphological characteristics and molecular evidence. Geastrum artocarpicola is characterized by shallowly saccate to deep saccate exoperidium, bubble-shaped to flask shaped basidia, spherical basidiospores. G. fibulatum is characterized by shallowly saccate to deep saccate exoperidium, spherical basidiospores, generative hyphae with clamp connections in the mycelium layer. G. sinense has arched exoperidium, long stipe expanded basidiomata, and spherical basidiospores. G. trachelium has deep saccate exoperidium, flask-shaped basidia, and spherical basidiospores. Sequences of the internal transcribed spacers (ITS), large subunit (nrLSU), the largest subunit of ribosomal polymerase II (RPB1), and subunit 6 of ATP synthase (ATP6) of the nuclear ribosomal DNA (rDNA) markers of the studied samples were generated, and the phylogenetic analyses were performed with maximum likelihood, maximum parsimony and Bayesian inference methods. The results showed that our collection clustered within Geastrum but distinctly from the others. Full morphological descriptions, illustrations, and phylogenetic analyses results for the four new species are provided. In addition, G. sanglinense is treated as a synonym of beijingense.